Sobre Alexandra Délano Alonso, Benjamin Nienass, Alicia de los Ríos Merino y María De Vecchi Gerli (eds.), Las luchas por la memoria contra las violencias en México - Badilla Rajevic, Manuela (El Colegio de México, A.C., 2025)
-